Host Genetic Associations with Salivary Microbiome in Oral Cancer. (May 2022) - Yang, S.F.; Lin, C.W.; Chuang, C.Y.; Lee, Y.C.; Chung, W.H.; Lai, H.C.; Chang, L.C.; Su, S.C.
Despite the growing recognition of a host genetic effect on shaping gut microbiota composition, the genetic determinants of oral microbiota remain largely unexplored, especially in the context of oral diseases. Here, we performed a microbiome genome-wide association study in 2 independent cohorts of patients with oral squamous cell carcinoma (OSCC, n = 144 and 67) and an additional group of noncancer individuals ( n = 104). Besides oral bacterial dysbiosis and signatures observed in OSCC, associations of 3 loci with the abundance of genus-level taxa and 4 loci with β diversity measures were detected ( q < 0.05) at the discovery stage. The most significant hit (rs10906082 with the genus Lachnoanaerobaculum, P = 3.55 × 10 –9 at discovery stage) was replicated in a second OSCC cohort. Moreover, the other 2 taxonomical associations, rs10973953 with the genus Kingella ( P = 1.38 × 10 –9 ) and rs4721629 with the genus Parvimonas ( P = 3.53 × 10 –8 ), were suggestive in the meta-analysis combining 2 OSCC cohorts. Further pathway analysis revealed that these loci were enriched for genes in regulation of oncogenic and angiogenic responses, implicating a genetic anchor to the oral microbiome in estimation of casual relationships with OSCC. Our findings delineate the role of host genotypes in influencing the structure of oral microbial communities.